Precision medicine in myocardial infarction: Nanotheranostic strategies - Alexander Shao‐Rong Pang; Vishalli Dinesh; Natalie Yan‐Lin Pang; Tarini Dinesh; Kimberley Yun‐Lin Pang; George W. Yip; Boon Huat Bay; Dinesh Kumar Srinivasan (Nano Select, 2024)
Abstract Myocardial infarction (MI) is the most prevalent non‐communicable disease worldwide. Nanotheranostics have made significant progress in the biomedical field, presenting an avenue to overcome the limitations of conventional approaches towards MI, in which personalized interventions have enhanced nanotherapeutic efficacy. The pharmacokinetics and pharmacodynamics of nanoscale materials have been modified through alteration of their physical and chemical properties such as structure, size, and surface, thereby improving target sensitivity and specificity. This revolutionary technology has also been accomplished through precision therapeutics in MI. In this review, we discuss advanced nanoparticle designs utilized in the diagnosis and treatment of MI that could be applied to deliver personalized treatment and improve patient outcomes.